CONTRIBUTION OF SÃO TOMÉ AND PRINCIPE NGOs IN TRAINING IN ENVIRONMENTAL EDUCATION: A PERCEPTION OF THE POPULATION - Andrade, Hilária; Rodrigues, Maria José (Cadernos de Educação Tecnologia e Sociedade, 2020)
Sao Tome and Principe is a country facing several environmental problems, including overexploitation of resources, waste treatment, soil erosion, among others. It is in this context that various NGOs have developed actions in the field of environmental education (EA). For this study, we worked with three NGOs from Santos and our main objective is to know the perception of the population about the work developed by these NGOs, within the scope of EA. This work is qualitative, interpretative and descriptive in nature. For data collection, we used the semi-structured interview with elements of the communities in the NGO intervention area. We found that respondents were unwilling to collaborate and afraid to participate in the interview. We note that this situation is justified by the infrequent investigations of this nature being conducted in Sao Tome and Principe. The results show that the population recognizes the work that has been developed within the scope of EE, mainly in the change of practices by the inhabitants, and the acquisition of attitudes and behaviors compatible with sustainable development. They value the preservation and use of natural resources, the main sources of wealth in Sao Tome and Principe. They stress that the work done by NGOs has improved the quality of life and the economy of families. We conclude that the intervention of NGOs of environmental nature are fundamental and has developed several awareness actions and, thus, contribute to improving people's quality of life towards more sustainable development.